Crime, criminal justice and criminology in Belgium. (March 2013) - Daems, Tom; Maes, Eric; Robert, Luc
For criminologists, Belgium is at once an interesting and a very complex country. Belgium is one of the first European countries where criminology became institutionalized in the universities. As for criminal justice, in many ways Belgium can be situated in the European middle. One feature of Belgium is its institutional complexity, with a push towards devolving decision-making powers from the federal level to its entities. This recently led to the longest period of post-election government negotiations in a democratic country: for more than 500 days, the country had no real federal government. Current agreements on a future sixth reform of the federal state include devolving matters of justice to the regions and language-based communities. Moreover, since the mid-1990s Belgium has been going through a period of unprecedented criminal justice reform, in various key areas such as policing, the prison system and victim policy. However, the persistent overcrowding of Belgian prisons has hampered various reform efforts and has determined the course of penal policy in recent decades.